La(iii) biodistribution profiles from intravenous and oral dosing of two lanthanum complexes, La(dpp)3 and La(XT), and evaluation as treatments for bone resorption disorders. Issue 7 (31st May 2017) - Weekes, D. M.; Cawthray, J. F.; Rieder, M.; Syeda, J.; Ali, M.; Wasan, E.; Kostelnik, T. I.; Patrick, B. O.; Panahifar, A.; Al-Dissi, A.; Cooper, D.; Wasan, K. M.; et al.
Abstract : Two La 3+ containing compounds are tested in vivo as potential oral treatments for osteoporosis. Abstract : Trivalent lanthanum (La 3+ ) has the potential to treat bone resorption disorders (such as osteoporosis) by eliciting a bone-building response in the cells which control skeletal remodelling. Because La 3+ suffers from extremely poor intestinal absorption, specifically designed chelators are required in order that a biologically active form of lanthanum can be administered orally. Two such chelators, 1, 2-dimethyl-3-hydroxy-4-pyridinone (Hdpp) and bis-{[bis(carboxymethyl)amino]methy}phosphinic acid (H5 XT), have previously been the subjects of extensive physical, in vitro, and in vivo testing as the tris- and mono-lanthanum(iii ) complexes La(dpp)3 and La(XT), respectively. In this manuscript, we expand upon those studies to include 4-week intravenous (IV) and oral La 3+ biodistribution profiles, which show that the metal ion initially accumulates in the liver followed by preferential redistribution and retention by bone. Of the two compounds, La(XT) demonstrates the more favourable in vivo characteristics, therefore dose-dependent oral biodistribution studies were carried out with this complex. These show drug saturation above a dose of 100 mg kg −1 day −1, so liver histology was performed in order to assess any potential toxicity. Finally, we improve upon the physical characterization of La(dpp)3 to include a single crystal X-ray structure, which exhibits an 8-coorindate La 3+ centre with two bound water molecules, and a disordered exoclathrate-type hydrogen bonded network.